Apoptotic Cell Death in Ewe Endometrium during the Oestrous Cycle - BENBIA, S.; BELKHIRI, Y.; YAHIA, M. (Journal of the Hellenic Veterinary Medical Society, 2020)
We hypothesized that endometrial tissues from ewes undergo spatial and temporal changes. Thus, two regulatory events were investigated in this study: cell death (apoptosis) and cell proliferation. Uteri were obtained from healthy ewes at Batna abattoir (Algeria). Based on macroscopic observation of the ovaries and plasma progesterone, uteri were assigned to follicular, early and active luteal phases. Apoptosis and proliferation were assessed by detection of cleaved caspase-3 and Ki-67, respectively. Ki-67 and cleaved caspase-3 (CCP-3) were expressed in both phases of the oestrous cycle and all endometrium cells types [luminal epithelia (LE), superficial gland epithelia (SG) and deep gland epithelia (DG)]. Immunohistochemistry for cleaved caspase-3 revealed few or no apoptotic stained cells in all endometrium locations during the entire oestrous cycle. However, Ki-67 was significantly higher in the follicular phase than in the early and active luteal phase. Besides, expression of CCP-3 in LE was higher than in SG and DG at the follicular phase and early luteal phase. However, Ki -67 and CCP-3 levels in all endometrium cells types did not significantly change at active luteal phase. Therefore, it is concluded that apoptosis and proliferation were occurred in ewe endometrium in a cyclic pattern and under the influence of the endocrine profile.